The Strategic Formulation for the Development of Al-Qur'an Education at MIQ Bustanul Ulum Losari Gudo Jombang - Khunaifi, A'an Yusuf; Fitri, Agus Zaenul; Sulistyorini, Sulistyorini (Jurnal Ilmiah Iqra', 2024)
Research on the strategic formulation of the Qur'an memorization program needs to be carried out. The findings obtained can be a foothold for application in strategic formulation to maintain existence and increase competitiveness between Islamic educational institutions. The research here aims to describe the strategic formulation of the Qur'an memorization program at Madrasah IslamiyahI Qur'an (MIQ) Gudo Jombang. Qualitative research methods, data collection techniques using observation, interviews, and documentation. The data validity technique uses triangulation. This research is focused on three research focuses, namely: (1) Strategic analysis of the Qur'an memorization program through SWOT analysis. (2) Strategic Planning through the right vision, mission, goals, and objectives. (3) Selection of strategies in the Qur'an memorization program to increase competitiveness and maintain the existence of madrasas. TPQ Bustanul Ulum is part of the business unit strategy managed by MIQ Gudo Jombang to improve the program of memorizing the Qur'an. The strategy formulation implemented is to take advantage of strengths and opportunities to become a superior strategy to expand the market and create competitiveness and be able to close the shortcomings and challenges of competitors.